The effect of selective estrogen receptor modulators on type 2 diabetes onset in women: Basic and clinical insights - Xu, Beibei (J Diabetes Complications, 2017)
Selective estrogen receptor modulators (SERMs) are a class of compounds that interact with estrogen receptors (ERs) and exert agonist or antagonist effects on ERs in a tissue-specific manner. Tamoxifen, a first generation SERM, is used for treatment of ER positive breast cancer. Raloxifene, a second generation SERM, was used to prevent postmenopausal osteoporosis. The third-generation SERM bazedoxifene (BZA) effectively prevents osteoporosis while preventing estrogenic stimulation of breast and uterus. Notably, BZA combined with conjugated estrogens (CE) is a new menopausal treatment. The menopausal state predisposes to metabolic syndrome and type 2 diabetes, and therefore the effects of SERMs on metabolic homeostasis are gaining attention. Here, we summarize knowledge of SERMs’ impacts on metabolic, homeostasis, obesity and diabetes in rodent models and postmenopausal women.